Does the Dual Mobility Cup Reduce Dislocation After Primary Total Hip Arthroplasty in Elderly Patients at High Risk of Dislocation?. Issue 2 (7th December 2022) - Chen, Mingliang; Takahashi, Eiji; Kaneuji, Ayumi; Tachi, Yoshiyuki; Fukui, Makoto; Orita, Yugo; Ichiseki, Toru; Zhou, You; Kawahara, Norio
Abstract : Objective: The dual mobility cup (DMC) is designed to extend the longevity of the prosthesis by improving stability, enhancing the range of motion, and decreasing impingement without increasing wear. We hypothesized that DMC would reduce the risk of dislocation in elderly patients. This study aimed to investigate the clinical and radiographic outcomes of DMC‐total hip arthroplasty (THA) in elderly patients at high risk of dislocation. Methods: From June 2016 to March 2020, 94 patients with a mean age of 77.7 years (97 hips) who underwent a posterolateral approach for DMC‐THA in our department were followed up for at least one year. Preoperative and postoperative pelvic tilt angles (PTA) and DMC orientation were prospectively collected for all patients. Intraoperative and postoperative complications were recorded. A parametric test was used for normal distribution, and a non‐parametric test was used for non‐normal distribution. Results: Abduction and anteversion angles of the cup were 42.4 and 18.0° in the supine position immediately postoperative. The average PTA for patients in the supine and standing positions were 26.5 and 34.5°, respectively. When moving from the supine to the standing position, patients experienced a mean posterior pelvic tilt of 9°. No intraoperative acetabular‐related complications were recorded. Postoperative complications included early infection in one patient (1.0%) and dislocation in one patient (1.0%). Conclusion: Our study demonstrates that DMC‐THA provides satisfactory short‐term outcomes in elderly patients at a high risk of dislocation, regardless of the change in PTA resulting from postural transition. Abstract : We hypothesized that dual mobility cup (DMC) would help elderly patients avoid dislocation. Additionally, we analyzed the clinical and radiographic outcomes of DMC‐total hip arthroplasty (THA) in elderly patients at high risk of dislocation due to pelvic tilt. The results indicate that DMC‐THA has satisfactory short‐term outcomes in elderly patients at high risk of dislocation, regardless of the change in pelvic tilt angle caused by the patient's position change.